Golgi membrane dynamics and lipid metabolism - Bankaitis, V.; Garcia-Mata, R.; Mousley, Carl (2012)
The striking morphology of the Golgi complex has fascinated cell biologists since its discovery over 100 years ago. Yet, despite intense efforts to understand how membrane flow relates to Golgi form and function, this organelle continues to baffle cell biologists and biochemists alike. Fundamental questions regarding Golgi function, while hotly debated, remain unresolved. Historically, Golgi function has been described from a protein-centric point of view, but we now appreciate that conceptual frameworks for how lipid metabolism is integrated with Golgi biogenesis and function are essential for a mechanistic understanding of this fascinating organelle. It is from a lipid-centric perspective that we discuss the larger question of Golgi dynamics and membrane trafficking. We review the growing body of evidence for how lipid metabolism is integrally written into the engineering of the Golgi system and highlight questions for future study. © 2012 Elsevier Ltd.